Changes in the Mechanical Axis and Weight-Bearing Line of the Ankle After Varus Knee Correction. Issue 4 (16th October 2019) - Lee, Seung Yeol; Kwon, Soon-Sun; Lee, Kyoung Min
Category: Ankle, Hindfoot Introduction/Purpose: Varus limb malalignment results in an imbalance of force transmission to the knee joint, resulting in a concentrated load in the medial compartment. A varus knee correction may affect the ankle and subtalar joint, because the weight-bearing load on the lower extremity extends from the hip to the foot. A previous study suggested that the true mechanical axis of the lower limb should be calculated with a line from the center of the femoral head to the lowest point of the calcaneus, not to the center of the tibial plafond. Therefore, we performed this study to evaluate changes in the mechanical axis and weight- bearing line of the ankle after varus knee correction. Methods: Patients with a varus knee who were followed-up after they had undergone high tibial osteotomy (HTO) or total knee replacement arthroplasty (TKA) at an age of >20 years, and who had undergone preoperative and postoperative scanogram were included in this study. The hip-knee-ankle (HKA) angle, mechanical axis, and weight-bearing line (line from the center of the femoral head to the lowest point of the calcaneus) were measured on the radiographs. The point at which the mechanical axis and weight-bearing line passed through the tibial plafond was the ankle joint axis point. The postoperative change in the ankle joint axis point on the mechanical axis and weight-bearing line according to the HKA angle correction was adjusted by multiple factors using a linear mixed model. Results: A total of 257 limbs from 198 patients were included in this study. The preoperative HKA was 7.3 ± 4.7° and corrected to 0.4 ± 3.8°. Although the ankle axis points on both axes moved laterally after HTO and TKA, the ankle joint axis of the weight- bearing line showed a significant larger lateral movement (22.5±35.7%) (Fig.) than that of the mechanical axis (15.7±16.0%) in terms of rate of change (p = 0.006). The ankle joint axis point on the weight-bearing line moved laterally by 0.9% per degree of postoperative HKA angle decrease (p < 0.001). The change in the ankle joint axis point on the mechanical axis was not statistically significant after HTO and TKA (p = 0.223). Conclusion: The mechanical axis and weight-bearing line of the ankle moved laterally after the varus knee correction. The ankle joint axis on the weight-bearing line moved laterally as the HKA angle decreased after the surgery, whereas the varus knee correction did not significantly affect the ankle joint axis on the mechanical axis. The varus knee correction might affect the subtalar joint as well as the ankle joint. Therefore, we believe that our findings warrant consideration in pre- and postoperative evaluations using the weight-bearing line of patients undergoing varus knee correction.